Effective extraction of fluoroquinolones from water using facile modified plant fibers - Nan Zhang; Yan Gao; Kangjia Sheng; Wanghui Jing; Xianliang Xu; Tao Bao; Sicen Wang (Elsevier, 2022)
In this study, ecofriendly and economic carboxy-terminated plant fibers (PFs) were used as adsorbents for the effective in-syringe solid phase extraction (IS-SPE) of fluoroquinolone (FQ) residues from water. Based on the thermal esterification and etherification reaction of cellulose hydroxy with citric acid (CA) and sodium chloroacetate in aqueous solutions, carboxy groups grafted onto cotton, cattail, and corncob fibers were fabricated. Compared with carboxy-terminated corncob and cotton, CA-modified cattail with more carboxy groups showed excellent adsorption capacity for FQs. The modified cattail fibers were reproducible and reusable with relative standard deviations of 3.2%-4.2% within 10 cycles of adsorption-desorption. A good extraction efficiency of 71.3%-80.9% was achieved after optimizing the extraction condition. Based on carboxylated cattail, IS-SPE coupled with ultra-performance liquid chromatography with a photodiode array detector was conducted to analyze FQs in environmental water samples. High sensitivity with limit of detections of 0.08-0.25 μg/L and good accuracy with recoveries of 83.8%-111.7% were obtained. Overall, the simple and environment-friendly modified waste PFs have potential applications in the effective extraction and detection of FQs in natural waters.